Exponentially weighted moving average chart as a suitable tool for nuchal translucency quality review - Hynek, Martin; Smetanová, Dagmar; Stejskal, David; Zvárová, Jana (Prenatal diagnosis, 2014)
OBJECTIVES: This study aimed to design an exponentially weighted moving average (EWMA) chart for the quality review of nuchal translucency (NT) and to assess its performance compared with the methods currently in use: retrospective distribution-based methods and the cumulative sum (CUSUM) chart. METHODS: The EWMA model was designed for NT quality review using simulation. The NT measurements obtained during routine first-trimester screening in our centre over a two-and-a-half-year period were retrieved from the database. The NT distribution parameters, EWMA and CUSUM chart were established, and the methods were compared. RESULTS: On the basis of the results from the simulation, the optimal EWMA settings were established. A set of 9338 NT measurements obtained from nine sonographers was used to construct the EWMA and CUSUM charts and to calculate the distribution parameters. Distribution-based methods were unable to reveal the temporal periods of poor performance. The EWMA model agreed closely with the CUSUM but had the advantage promptly indicating when the process returned to an in-control state, thus extending its use to long-term prospective and retrospective quality assessments. CONCLUSIONS: The EWMA provides a universal, easy and efficient tool for NT quality review when the prompt and effective detection of suboptimal performance is desired.
Keywords: Models, Statistical; statistické modely; Crown-Rump Length; těhotenství; Adult; dospělí; Female; Quality Assurance, Health Care; zajištění kvality zdravotní péče; Pregnancy; Humans; ženské pohlaví; lidé; Nuchal Translucency Measurement; měření nuchální translucence; temenokostrční délka